SILAGEM DE CAPIM-ELEFANTE BRS CAPIAÇU COM ADIÇÃO DE FUBÁ DE MILHO NA ENSILAGEM - INDIRA DAIANE LEDESMA SANTOS (2024)
BRS Capiaçu elephant grass is a cultivar with high production potential and adapted to different climatic conditions in Brazil. Developed by Embrapa Gado de Leite, this perennial grass stands out for its erect clumps, wide leaves and thick stems, in addition to being resistant to water stress and tipping over, facilitating mechanical harvesting. Recommended for deep, well-drained soils, its propagation occurs through culms, and planting is recommended at the beginning of the rainy season. BRS Capiaçu elephant grass silage appears as an advantageous alternative for animal feed, especially during periods of scarcity, such as winter. However, challenges such as low light and colder temperatures can impact your production at this time of year. To overcome these challenges, the gradual addition of cornmeal as an absorbent additive has proven to be an effective practice. With the aim of obtaining more information about the production of silage from BRS Capiaçu elephant grass in the winter period, work was carried out with the gradual addition of corn meal (0%, 5%, 10%, 15% and 20%) as an absorbent additive in elephant grass silage cv. BRS Capiaçu. The results revealed that the increase in the amount of cornmeal caused a significant linear increase in the dry matter (DM), starch, non-fibrous carbohydrates (NFC) and total digestible nutrients (TDN) contents of the silages, while there was a linear reduction in fibrous fractions (NDF, FDA, LIG). The chemical-bromatological composition of the silages showed that higher levels of corn meal inclusion resulted in higher levels of crude protein, important for animal nutrition, and lower concentrations of fiber, which can increase the digestibility of the silage. The fermentation profile of the silages was also evaluated, showing that the inclusion of corn meal did not compromise fermentation, with a predominance of lactic acid, essential for an adequate fermentation process and for the preservation of silage nutrients.